Molecular Events Controlling Cessation of Trunk Neural Crest Migration and Onset of Differentiation - Lee, Vivian M.; Hernandez, Sergio; Giang, Belle; Chabot, Chris; Hernandez, Jazmir; de Bellard, Maria Elena (Frontiers in Cell and Developmental Biology, 2020)
Neural crest cells migrate extensively in vertebrate embryos to populate diverse derivatives including ganglia of the peripheral nervous system. Little is known about the molecular mechanisms that lead migrating trunk neural crest cells to settle at selected sites in the embryo, ceasing their migration and initiating differentiation programs. To identify candidate genes involved in these processes, we profiled genes up-regulated in purified post-migratory compared with migratory neural crest cells using a staged, macro-arrayed cDNA library. A secondary screen of in situ hybridization revealed that many genes are specifically enhanced in neural crest-derived ganglia, including macrophage migration inhibitory factor (MIF), a ligand for CXCR4 receptor. Through in vivo and in vitro assays, we found that MIF functions as a potent chemoattractant for neural crest cells. These results provide a molecular profile of genes expressed concomitant with gangliogenesis, thus, offering new markers and potential regulatory candidates involved in cessation of migration and onset of differentiation.